Existence, Uniqueness and Stability Results for Impulsive Neutral Stochastic Functional Differential Equations with Infinite Delay and Poisson Jumps - Anguraj, A.; Banupriya, K. (Discontinuity, Nonlinearity, and Complexity, 2026)
In this paper, we study the existence and uniqueness of mild solutions of impulsive neutral stochastic functional differential equations with infinite delay and Poisson jumps under non-Lipschitz conditionwith Lipschitz condition being considered as a special case by means of the successive approximation. Further, We study the continuous dependence of solutions on the initial value by means of a corollary of the Bihari inequality.